Update on Meniscus Debridement and Resection - Weiss, William M.; Johnson, Don (The Journal of Knee Surgery, 2014)
Arthroscopic treatment of meniscal pathology is among the most common procedures performed by orthopedic surgeons, and has evolved from open total meniscectomy to arthroscopic partial meniscectomy and repair. With knowledge of the importance of the meniscus to articular cartilage preservation, efforts to preserve the meniscus with repair have been increasing, but this is not appropriate for all patients. The decision of whether to perform meniscal debridement or repair must be made on an individual basis, and characteristics of both the patient and tear should be considered. Important patient characteristics include age, cartilage status, concomitant anterior cruciate ligament reconstruction, and compliance. Tear characteristics that influence healing ability include location, morphology, acuity, and stability. Results from the literature indicate that outcomes of partial meniscectomy are superior to total, and that arthroscopic debridement of the meniscus is an effective treatment in appropriate patients. Symptomatic meniscal tears that are not likely to heal are better treated with partial meniscectomy than repair. The determination of which patients and meniscal tears are appropriate for meniscal debridement or repair should be made on an individual basis, in consultation with the patient, based on the factors presented.
Keywords: meniscus; meniscectomy; debridement; meniscus tear; knee arthroscopy